Real-Estate Agent Commission Structure and Sales Performance - Pieter Gautier; Arjen Siegmann; Aico van Vuuren (Tinbergen Institute, 2017)
Do higher real-estate agent fees imply better performance? This study uses a nation-wide data set of residential real-estate transactions in the Netherlands from 1985 to 2011 to provide evidence against this. Brokers with a flat-fee structure who charge an up-front fee (which is substantially lower than the average fee of traditional brokers) and leave the viewings to the seller sell faster and at - on average - 2.7 percent higher prices. We correct for fixed house- and time effects. We provide additional evidence that the price dfference is not due to a seller-selection effect.
Keywords: D80; L10; L80; R20; R30; 330; real-estate brokers; broker incentives; housing; agency